2023
DOI: 10.3390/molecules28073239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Flavone Derivative Displaying a 4′-Aminophenoxy Moiety as Potential Selective Anticancer Agent in NSCLC Tumor Cells

Abstract: Five heterocyclic derivatives were synthesized by functionalization of a flavone nucleus with an aminophenoxy moiety. Their cytotoxicity was investigated in vitro in two models of human non-small cell lung cancer (NSCLC) cells (A549 and NCI-H1975) by using MTT assay and the results compared to those obtained in healthy fibroblasts as a non-malignant cell model. One of the aminophenoxy flavone derivatives (APF-1) was found to be effective at low micromolar concentrations in both lung cancer cell lines with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A series of new heterocyclic derivatives were recently synthesized via the functionalization of a flavone ring with an aminophenoxy moiety in different positions of the A ring and a phenoxy moiety in different positions of the B ring [ 34 ]. Their cytotoxicity was investigated in vitro against two human non-small cell lung cancer (NSCLC) cell lines (A549 and NCI-H1975).…”
Section: Biological Activity Of Flavones Flavonols and Auronesmentioning
confidence: 99%
See 3 more Smart Citations
“…A series of new heterocyclic derivatives were recently synthesized via the functionalization of a flavone ring with an aminophenoxy moiety in different positions of the A ring and a phenoxy moiety in different positions of the B ring [ 34 ]. Their cytotoxicity was investigated in vitro against two human non-small cell lung cancer (NSCLC) cell lines (A549 and NCI-H1975).…”
Section: Biological Activity Of Flavones Flavonols and Auronesmentioning
confidence: 99%
“…A flavone derivative containing a phenoxy moiety at the C’3 position of the B ring and a p -aminophenoxy group at the sixth position of the A ring was the most effective, presenting micromolar IC 50 values (for A549 and H1975) and a high selectivity index (SI > 10, Table 1 , line 10). Further flow cytometric analyses showed that this compound induces apoptosis and cell cycle arrest in the G2/M phase through the up-regulation of p21 expression [ 34 ]. The absence of the phenoxy moiety on the B ring and the different position of the p -aminophenoxy moieties on the A ring decreased the efficacy and selectivity of aminophenoxy derivatives [ 34 ].…”
Section: Biological Activity Of Flavones Flavonols and Auronesmentioning
confidence: 99%
See 2 more Smart Citations